Prenatal diagnosis of Simpson-Golabi-Behmel syndrome type 1 with an 814 kb Xq26.2 deletion with the initial presentation of a thick nuchal fold - Hsiu-Huei Peng; Chung Jen Yu; Yi Chi Chen; Chin-Chieh Hsu; Shuenn-Dyh Chang; Ho-Yen Chueh; Yao-Lung Chang; Po-Jen Cheng; Yen-Chang Lee (Elsevier, 2023)
Objective: Simpson-Golabi-Behmel syndrome type 1 (SGBS1) is a rare X-linked recessive disorder characterized by overgrowth and multiple anomalies. Most clinical diagnoses of SGBS1 are made postnatally. We present the case of a pregnant woman in whom the fetus presented with a thick nuchal fold 5.6 mm at 15 weeks of gestation, leading to the prenatal diagnosis of SGBS1 with Xq26.2 (133408101-134221889) deletion. Case report: We report the case of a 34-year-old pregnant woman with the initial presentation of fetal thick nuchal fold 5.6 mm at 15 weeks of gestation. Amniocentesis of the fetal karyotype revealed a normal 46, XY, and single nucleotide polymorphism array showed Xq26.2 (133408101-134221889) deletion. Prenatal ultrasound at 21 weeks of gestation revealed a thick nuchal fold, hepatomegaly, nephromegaly, congenital diaphragmatic hernia, hypospadias, and polyhydramnios. Fetal magnetic resonance imaging revealed hepatomegaly, nephromegaly, congenital diaphragmatic hernia, and right lung hypoplasia. The woman had her pregnancy terminated at 24 weeks of gestation. The proband had a general appearance of low-set ears, hypertelorism, a large tongue, and hypospadias and some unique findings on autopsy, including hepatomegaly, right hiatal hernia, liver extensive extramedullary hematopoiesis, kidney marked congestion, and focal hemorrhage. Discussion: The main prenatal ultrasound findings that alert clinical doctors about the possible diagnosis of SGBS1 included macrosomia, polyhydramnios, organomegaly, renal malformations, congenital diaphragmatic hernia, and cardiac anomalies. Our case underscores the importance of fetal karyotyping combined with single nucleotide polymorphism array when a thick nuchal fold is found. Genetic counseling is essential in SGBS1, and prenatal testing or preimplantation testing for subsequent pregnancies is necessary to identify possible pathogenic variants.